(untitled) (Tanzania Medical Journal, 2023)
Background Neonatal jaundice is a common morbidity encountered during the first week of life. The causes of which are variable with an underlying pathology and if left unchecked can lead to bilirubin-induced encephalopathy and its antecedent long-term neurological sequelae. There is limited data on prevalence, factors associated with neonatal jaundice and the validity of using clinical assessment of neonatal jaundice in Tanzania. Objective To determine the proportion of neonates admitted with jaundice, factors associated, and the validity of the clinical assessment of neonatal jaundice at Muhimbili National Hospital. Methodology A hospital-based cross-sectional study at the neonatal unit of MNH from December 2018 to February 2019. Jaundiced infants were investigated for levels of bilirubin and other laboratory parameters. Frequencies and percentages, along with Chi-square tests and logistic regression analysis were done. The coefficient of Correlation of the Laboratory levels and Kramer’s criteria was also done with Receptor Observation Curves (ROC) made for the parameters. Results Neonatal jaundice was found in 51.1% of the 432 enrolled participants. Term infants were 51.4%. Factors associated with neonatal jaundice were ABO incompatibility, rhesus incompatibility, sepsis, peripheral hemolysis, and positive coombs test. The level of jaundice correlated well with the clinical assessment of jaundice. The sensitivity of clinical assessment was found to be 51.1% with a specificity of 100% and correlated well with the laboratory findings as calculated from the ROC curve. Conclusion Neonatal jaundice is very common in our unit and the commonest cause is ABO incompatibility and Sepsis. Clinical assessment is still a very reliable method of assessment of neonatal jaundice. A proper clinical judgement using Kramer’s rule should be supplemented and confirmed with a total serum bilirubin to increase the sensitivity.